KSHARSUTRA APPLICATION IN AURICULAR KELOID A CASE STUDY - Sarkar Suman; Mandal Asim Kumar; Gupta Mradu (International Journal of Applied Ayurved Research, 2019)
The Keloid is an overgrowth of fibrous tissue in a scar, occurred in susceptible individuals 1. It is characterize by excessive collagen following any local trauma, thereby leading to a cosmetically unaesthetic, scar formation and extending well beyond the boundaries of the original wound 2. It usually presents as firm nodules, often pruritic and painful, which do not regress spontaneously 3. The condition presents quite a therapeutic challenge due to its frequent invasion to adjacent normal dermis. Various treatment modalities like pressure therapy, intralesional steroid therapy, cryosurgery, radiation, laser therapy and surgical excision are generally performed for keloids, but there are not so much promising. It was always a challenge to a surgeon. The present paper is the case presentation of an auricular keloid of an adolescent Indian boy by intervention with Ksharsutra.